Neighbourhood planning, rural ageing and public health policy in England: a case of policy myopia?. Issue 3 (1st May 2022) - Lee, Caroline; Parker, Gavin; Buckner, Stefanie; Mattocks, Calum; Barnes, Amy; Oliver, Emily J.; Cowan, Andy; Lafortune, Louise
Abstract : This article draws together new research findings with recent evidence, theory and policy developments relating to place-based planning for health and well-being. It considers how neighbourhood planning (NP) can support the advancement of the ageing-well agenda and well-being goals in rural areas of England. We argue that NP can theoretically impact positively on age-friendly objectives (sensitive housing design, downsizing options, social and civic participation), but this is limited without greater incentives and political commitment to integrated policy making. Without due attention, the advancement of ageing well and rural well-being through NP, as currently constructed, will remain a largely missed opportunity.